Linguistic creativity and evaluation in news headlines (on the example of Wiadomości and Wydarzenia) - Zwolińska, Paulina (Linguistic creativity in marketing, 2022)
The main task of TV news services is to convey the news to the public. The language used by presenters and broadcasters has certain characteristics. The purpose of this article is to analyze the quantitative and qualitative headlines from ten major editions of two TV news services: „Wiadomości” and „Wydarzenia”. The author primarily study the evaluation of particular titles and the various language strategies used in them.